Bone Status in a Patient with Insulin-Like Growth Factor-1 Receptor Deletion Syndrome: Bone Quality and Structure Evaluation Using Dual-Energy X-Ray Absorptiometry, Peripheral Quantitative Computed Tomography, and Quantitative Ultrasonography - Pelosi, Paola; Lapi, Elisabetta; Cavalli, Loredana; Verrotti, Alberto; Pantaleo, Marilena; de Martino, Maurizio; Stagi, Stefano (Frontiers in Endocrinology, 2017)
Haploinsufficiency of the insulin-like growth factor (IGF)-1 receptor (IGF1R) gene is a rare, probably under-diagnosed, cause of short stature. However, the effects of IGF1R haploinsufficiency on glucose metabolism, bone status and metabolism have rarely been investigated. We report the case of a patient referred to our centre at the age of 18 months for short stature, failure to thrive, and Silver-Russell-like phenotype. Genetic analysis did not show hypomethylation of the 11p15. region or uniparental disomy of chromosome 7. Growth hormone (GH) stimulation tests revealed GH deficiency, whereas IGF-1 was 248 ng/mL. r-hGH treatment showed only a slight improvement (from -4.4 to -3.5 SDS). At 10 years of age, the child was re-evaluated: CGH-array identified a heterozygous de novo 4.92 Mb deletion in 15q26.2, including the IGF1R gene. Dual-energy X-ray absorptiometry (DXA) showed a normal bone mineral density (BMD) z-score, while peripheral quantitative computed tomography (pQCT) revealed reduced cortical and increased trabecular elements. A phalangeal bone quantitative ultrasonography (QUS) showed significantly reduced amplitude dependent speed of sound and bone transmission time values. The changes in bone architecture, quality, and metabolism in heterozygous IGF1R deletion patients, support the hypothesis that IGF-1 can be a key factor in bone modelling and accrual.